2012 Design, Automation &Amp; Test in Europe Conference &Amp; Exhibition (DATE) 2012
DOI: 10.1109/date.2012.6176640
|View full text |Cite
|
Sign up to set email alerts
|

Multi-core architecture design for ultra-low-power wearable health monitoring systems

Abstract: Abstract-Personal health monitoring systems can offer a costeffective solution for human healthcare. To extend the lifetime of health monitoring systems, we propose a near-threshold ultralow-power multi-core architecture featuring low-power cores, yet capable of executing biomedical applications, with multiple instruction and data memories, tightly coupled through flexible crossbar interconnects. This architecture also includes broadcasting mechanisms for the data and instruction memories to optimize system en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 13 publications
0
46
0
Order By: Relevance
“…Hardware/Software elements Low-power multi-core WBSNs (e.g. [11] and [15]) typically presents a structure comprising a set of computing units interfaced to instruction and data memories (IM and DM) through interconnection networks, as depicted in Figure 2. Three properties, common in this family of systems, must be satisfied by the platform to apply the proposed synchronization method.…”
Section: Synchronization Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Hardware/Software elements Low-power multi-core WBSNs (e.g. [11] and [15]) typically presents a structure comprising a set of computing units interfaced to instruction and data memories (IM and DM) through interconnection networks, as depicted in Figure 2. Three properties, common in this family of systems, must be satisfied by the platform to apply the proposed synchronization method.…”
Section: Synchronization Methodologymentioning
confidence: 99%
“…The authors of [11] and [15] have shown that, even in the field of embedded bio-signal analysis applications, where the computational demands are rather low, parallelism leads to high energy efficiency, especially when multiple cores can execute in lock-step, i.e. : they are at the same point of the program flow, so that a single instruction is fetched and delivered in parallel.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the operating voltages for a processor are limited to the minimum-voltage required for the reliable operation of on-chip SRAM cache which fails when scaling down to ultra-low voltages because of its shrinking noise margins, Nevertheless, SRAM dominates the energy consumption among the components of a processor [11] and several alternative SRAM bit-cells have been proposed. These sub-threshold SRAM bit-cells have 8-transistors [12] or 10-transistors [13]- [15].…”
Section: Introductionmentioning
confidence: 99%
“…To maximize the overall efficiency of smart WBSNs, signal processing must therefore be supported within a tight power budget, while at the same time respecting real time constraints. In this regard, many efforts have been made in the last years, proposing solutions ranging from ad-hoc accelerators [10], [11] to ultra-low-power (ULP) multi-core architectures [8], [12].…”
Section: Introductionmentioning
confidence: 99%